2022
DOI: 10.1155/2022/8954606
|View full text |Cite
|
Sign up to set email alerts
|

Causal Association of Thyroid Signaling with C-Reactive Protein: A Bidirectional Mendelian Randomization

Abstract: Context. Existing literature demonstrated that thyroid-stimulating hormone (TSH) and free thyroid hormone (fT4) were associated with the C-reactive protein (CRP), an inflammatory risk factor of cardiovascular diseases (CVD), but the causal relationship between them remained unclear. Methods. Based on the latest genome-wide association study summary data, bidirectional two-sample Mendelian randomization (MR) was employed to detect the causal relationship and effect direction between TSH, fT4, and CRP. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For exposures with two or more IVs, the study utilized the Inverse Variance Weighted (IVW) method. The IVW method operates by utilizing the reciprocal of the variance of each instrumental variable’s effect estimate as a weight, thereby assigning more weight to more precisely estimated effects ( Li et al, 2022 ). This method aggregates the weighted effect sizes of genetic variants to provide an overall estimate of the causal impact of the exposure on the outcome ( Chen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…For exposures with two or more IVs, the study utilized the Inverse Variance Weighted (IVW) method. The IVW method operates by utilizing the reciprocal of the variance of each instrumental variable’s effect estimate as a weight, thereby assigning more weight to more precisely estimated effects ( Li et al, 2022 ). This method aggregates the weighted effect sizes of genetic variants to provide an overall estimate of the causal impact of the exposure on the outcome ( Chen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…A bidirectional Mendelian randomization analysis showed that genetically elevated CRP was associated with an increase in both TSH and fT4, but there was no evidence that TSH or fT4 could have an impact on CRP; however, another study showed that TSH is not linked to CRP [ 644 , 645 ]. A case report shows that CRP had elevated values (approx.…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…This emerging epidemiological technique effectively mitigates potential confounding factors and interferences, enabling more robust causal conclusions compared to traditional observational studies ( 19 ). Previous research utilizing MR analysis has successfully demonstrated causal relationships between FT4 and TSH levels with C-reactive protein ( 20 ), age-related macular degeneration (AMD) ( 21 ), and atrial fibrillation ( 22 ). Building upon this foundation, our study utilizes a large-scale genome-wide association study (GWAS) to examine the causal relationship and risk between thyroid function and SSNHL by using a bidirectional and multivariable MR analysis.…”
Section: Introductionmentioning
confidence: 99%